'When Mayors make Migration Policy’: What role for cities in EU migration and integration policymaking? - Bendel, Petra; Heimann, Christiane; Schammann, Hannes; Stürner, Janina (2020)
EU institutions and a growing number of member states are starting to recognise municipal actors as important players in integration governance. However, moving away from ad hoc exchanges on integration towards more structural forms of cooperation, and opening up migration policy debates to local input remains challenging. Building on an analysis of the benefits of proactive cooperation between local authorities and EU institutions, this Policy Brief presents recommendations to (i) strengthen the local impact on supranational policymaking; (ii) link migration and integration policies through the inclusion of municipalities; and (iii) mitigate the urban-rural divid
Keywords: EU; migration; integration; municipal actors